Facile shape control of GdPO\(_4\).H\(_2\)O:Tb\(^{3+}\) by solvothermal method using di/polyethylene glycol as soft template - Nguyen, Thanh Huong; Pham Thi Lien,; Hoang Thi Khuyen,; Nguyen Thi Ngoc Anh,; Do Khanh Tung,; Nguyen Vu,; Dinh Manh Tien,; Nguyen Thanh Binh, (Communications in Physics, 2026)
Tb3+-doped GdPO4·H2O phosphors were synthesized with wire-, rod-, and particle-like morphologies using a solvothermal method. This was achieved by varying the reaction solvent between diethylene glycol (DEG) and polyethylene glycol (PEG) of different molecular weights. The crystal structure, morphology, and photoluminescence (PL) properties were characterized using X-ray diffraction (XRD), field-emission scanning electron microscopy (FESEM), and PL spectroscopy. The emission spectra showed the characteristic green luminescence of Tb³⁺ ions, with transition from the 5D4 → 7Fj (J = 6, 5, 4, 3) at 489, 543, 586, and 620 nm, respectively. Systematic analysis revealed a strong correlation between material morphology, crystal structure, and luminescence efficiency. The sample with a nanoparticle morphology, synthesized at 100 °C in a PEG 8000 medium, exhibited the highest PL intensity. It displayed a dominant green emission at 543 nm (5D4 → 7F5) and sharp, well-defined emission bands. These findings confirm that a solvent-mediated morphology control strategy is effective for optimizing the luminescence performance of GdPO4-based phosphors.